2013
DOI: 10.1068/c1101b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Causes of Informal and Formal Discretion in the Delivery of Enterprise Policies: A Multiple Case Study

Abstract: This research investigates a relevant gap in the academic literature on enterprise policy—namely, the nature of discretion and the causes that permit it during policy implementation. We found in our case studies that the programme workers who deliver policies exerted considerable discretion. Further evidence suggests that the main influences on what we call informal discretion—discretion clearly outside programme objectives—include the design of programme evaluation and audit as well as the influence of evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The emphasis was placed on the 'street-level bureaucrats' to ensure delivery of enterprise policy initiatives but numerous issues hindered effective implementation (lack of formal structures for implementation, complex relationships etc.). expectations were met or whether entrepreneurs and SMEs were given appropriate support and assistance to start-up and grow (Vega et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The emphasis was placed on the 'street-level bureaucrats' to ensure delivery of enterprise policy initiatives but numerous issues hindered effective implementation (lack of formal structures for implementation, complex relationships etc.). expectations were met or whether entrepreneurs and SMEs were given appropriate support and assistance to start-up and grow (Vega et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Communication between the government department and the RDA was based around deliverables, with significant weight attached to quantifiable objectives. The quantitative nature of capturing the targets failed to adequately evaluate and measure the implications of the policy initiatives being delivered (Vega et al, 2013) because often it was highlighted by the RDA that:…”
Section: Insert Table 3 Herementioning
confidence: 99%
“…There is now acceptance that, to varying degrees, actors are able to exercise choice over how they respond to institutional pressures, which includes not only compliance but also compromise, avoidance and outright defiance (Oliver, 1991). As a recent example of this, Vega et al, (2013) reported how officials were able to exercise informal discretion over the implementation of enterprise policy in spite of procedures in place to govern their behaviour.…”
Section: An Institutional Perspective On Sme-friendly Procurementmentioning
confidence: 99%
“…Recent analyses suggest that it may be attributable to the ways in which policy ideas originate and develop (Dennis Jr 2011; Williams 2013). Most of the enterprise policy literature has focused on the implementation (Mole 2002;Xheneti and Kitching 2011;Vega et al 2013) and evaluation stages (Storey 2002;Bennett 2008;Lenihan 2011;Cowie 2012;Jones et al 2013). Scholars such as Storey ( , 2002 and Bennett (2008) have concentrated on how and why enterprise policy should be assessed.…”
Section: Introductionmentioning
confidence: 99%